Deep Infiltrating Sigmoid Endometriosis: A Rare Case of Obscure Pathogenesis - Zacharioudakis, Georgios; Kiroplastis, Konstantinos; Bratko, Aikaterini; Petras, Panagiotis; Katsiki, Evangelia; Sidiropoulou, Maria; Kambaroudis, Apostolos (Archives of Clinical and Medical Case Reports, 2021)
Endometriosis is a serious disease affecting women, presenting three main variations. Its diagnosis and treatment are more than challenging. This is a rare case of deep infiltrating bowel endometriosis which contradicts current pathogenetic notions, based on its infiltration pattern. Pathogenesis of deeply infiltrating bowel endometriosis is ill-defined, entailing inoculation of endometrial tissue on the bowel wall mainly due to retrograde menstruation or coelomic metaplasia. This is an rare case of a patient who presented a single endometriotic bowel lesion, progressing from the inwards of the sigmoid colon, infiltrating a single lymph node.